Towards Improving the Efficiency and Level of Performance of Arabic language Teachers through Arabic Programs for non-Native Speakers in West Africa: Nigeria as a Case Study - Ahmad Garba (Tarbiatuna: Journal of Islamic Education Studies, 2023)
Arabic language teacher training program in Nigeria is one of the important elements in providing teachers with the necessary expertise to qualify for job opportunities within the educational sectors. This paper aims to discuss on the standards and competence of the Arabic teacher which he acquires through teacher education programs in Nigeria and the extent of their justifications by highlighting the aspects of training that Arabic language teachers deal with in the training institutions. Keywords: Arabic teachers, educational institutions, teacher education مستخلص البحثيعد البرنامج تدريب معلمي اللغة العربية في نيجيريا أحد العناصر المهمة في تزويد المعلمين بالخبرات اللازمة المؤهلة للحصول على فرص عمل في قطاعات التعليمية وهناك العديد من المراكز التعليمية لتدريب المعلمين المنتشرة في شتى الولايات النيجيرية وتتبع بعضها وزارة التربية والتعليم الفدرالية كما كانت بعضها تتبع وزارات التربية والتعليم التابعة للولايات، تهدف هذه الورقة تسليط الضوء على مدى مستوى القدرات والكفاءات لدى معلمي اللغة العربية في نيجيريا ومدى مبرراتها خلال إلقاء الضوء على جوانب التدريب التي يتناولها معلمو اللغة العربية في المؤسسات التدريبية الكلمات المفتاحية: معلمي اللغة العربية, مراكز التربوية, إعداد المعلم